2014
DOI: 10.1002/ijc.29348
|View full text |Cite
|
Sign up to set email alerts
|

Downstaging cancer in rural Africa

Abstract: Cancer is usually diagnosed late in rural Africa leading to incurability and abbreviated survival. Many curable cancers present on the body surface, often recognizable early by laymen as suspicious, justifying professional referral. Cancer diagnoses in two randomly chosen Tanzanian villages were compared after conventional dispensary self-referral vs. proactive visits in the home. Village navigators organized trips for professional consultation. In the control village 21% were self-referred, 20% of them were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 4 publications
0
48
0
Order By: Relevance
“…However, a limitation of this study is that it did not investigate a wider range of health service related factors such as misdiagnosis by health professionals, and delays in getting appointments and in obtaining test results. Stage migration interventions have proven to be successful and cost effective in several low- and middle-income countries such as India 45 , Malaysia 46 , South Africa 38 , Tanzania 47 and Sudan 48 following educational interventions coupled with appropriate diagnosis and treatment. In Sudan, the implementation of a cancer awareness and breast examination intervention program using trained local volunteers improved the early detection of breast abnormalities in women in rural communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a limitation of this study is that it did not investigate a wider range of health service related factors such as misdiagnosis by health professionals, and delays in getting appointments and in obtaining test results. Stage migration interventions have proven to be successful and cost effective in several low- and middle-income countries such as India 45 , Malaysia 46 , South Africa 38 , Tanzania 47 and Sudan 48 following educational interventions coupled with appropriate diagnosis and treatment. In Sudan, the implementation of a cancer awareness and breast examination intervention program using trained local volunteers improved the early detection of breast abnormalities in women in rural communities.…”
Section: Discussionmentioning
confidence: 99%
“…48 In Tanzania, late stage diagnosis (stages III/IV) was reduced by 51% over three years after trained health personnel delivered an educational intervention that focused on the signs and symptoms of cancer, and subsequently screened women by clinical examinations and taking pictures of suspicious lesions. 47 More research is needed to characterize delays and factors associated with diagnostic delays in Nigeria, as well as in other SSA populations 43 , as such knowledge is crucial to the development of context appropriate BC control programs.…”
Section: Discussionmentioning
confidence: 99%
“…Proactive visitation of health aides to the villages for the early detection of BC and other cancers was effective. The study found an increasing number of early-stage BCs (stages I and II) in the intervention villages during the 1st, 2nd, and 3rd year at 9%, 60%, and 67%, respectively [49]. …”
Section: Cancer Control In Africamentioning
confidence: 99%
“…Late stage at diagnosis is a problem for BC control [40,48,49]. In Ghana, a study showed that 64.1% of patients presented to facilities at a late stage of the disease for diagnosis [46].…”
Section: Cancer Control In Africamentioning
confidence: 99%
“…After 3 years, breast cancer downstaging was one of the most significant results of the program, evidenced by a 74% increase in stage I to II breast tumors. 27 …”
mentioning
confidence: 99%